Expanded newborn screening for inborn errors of metabolism by electrospray ionization-tandem mass spectrometry: results, outcome, and implications - Schulze, Andreas; Lindner, Martin; Kohlmüller, Dirk; Vill, Katharina; Mayatepek, Ertan; Hoffmann, Georg F. (Pediatrics, 2003)
Objective. The aims of this study were to determine the impact of expanded newborn screening using tandem mass spectrometry (MS/MS) on the overall detection rate of inborn errors of metabolism in Germany and to assess the outcome for the patients that were diagnosed. - Methods. During the period of study, 250 000 neonates in a German population were investigated for 23 inborn errors of metabolism by electrospray ionization-MS/MS. The overall value of the screening program was estimated by 1) complete ascertainment of all positive tests; 2) definite assignment of all diagnoses including reconfirmation at 12 months; and 3) clinical follow-up of all detected patients in an overall interval of 42 months. The mean observation period was 13.5 months per child. - Results. In 106 newborns, confirmed inborn errors of metabolism were found. The disorders were classified as 50 classic forms and 56 variants. A total of 825 tests (0.33%) were false-positives. Seventy of the 106 newborns with confirmed disorders were judged to require treatment. Six children developed symptoms despite treatment. Three children had died. Among 9 children who became symptomatic before report of the results of screening, in 6 the diagnosis had been made in advance of the screening report. In evaluation of the screening program, 61 of the 106 identified children (58% of true-positives, or 1 of 4100 healthy newborns) were judged to have benefited from screening and treatment, because the diagnosis had not been made before screening. None of these infants had died and none developed psychomotor retardation or metabolic crisis during the follow-up period. - Conclusions. The screening by MS/MS for up to 23 additional disorders has approximately doubled the detection rate compared with that achieved by the conventional methods used in Germany. This strategy represents valuable preventive medicine by enabling diagnosis and treatment before the onset of symptoms.
Gesehen am 21.12.2020